Organic Carbon Pools in Permafrost-Affected Soils of Siberian Arctic Regions - Zubrzycki, Sebastian (Staats- und Universitätsbibliothek Hamburg Carl von Ossietzky, 2013)
Permafrost-affected soils of the Lena River Delta (Northern Siberia) and its hinterland are characterized by a high diversity. The three main soil groups of the permafrost-affected soils, which are organic-rich Histels, cryoturbated Turbels and mineral and non-cryoturbated Orthels, include a large variety of subgroups. This variability formed while time, temperature, and water saturation strongly slowed the soil-forming processes. These diverse North-Siberian soils have been only scarcely investigated by soil scientists so far, although they play a major role in global long-term carbon sequestration. Permafrost-affected soils started to attract broader attention since increasing knowledge about the carbon storage of these soils has been coupled with future climate trend projections indicating the potential of a positive feedback loop of warming when the predicted release of “permafrost carbon” will increase the greenhouse effect. Despite their small thickness of few decimetres, these soils and their carbon storage might play an important role in affecting the future climate when one considers the projected increases of temperature and recent models of the active layer depth development. The question if they are still sequestering carbon is still controversially discussed and will have different answers for different permafrost regions. Approaches to determine the carbon source and sink functions of permafrost-affected soils require robust knowledge of the recent carbon storage of these soils, which is where this thesis begins. Here the author provides the first robust estimates of the carbon storage of the modern, Holocene geomorphologic units of the Lena River Delta as well as estimates of the carbon stocks of the seasonally thawed layer from a latitudinal transect in Northeast-Siberia extending from the Lena River Delta into its hinterland. For the area of the Lena River Delta, he also reports total nitrogen stocks. The Lena River Delta, which is the largest delta in the Arctic, extends over an area of 32,000 ...